Pengembangan Game Berpikir Komputasional Berbasis Website Bagi Peserta Didik Kelas IV SDN Margaluyu - Tantan Nugraha Tantan; Dian Rinjani; Agus Juhana (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2023)
The research aimed at (1) Introducing the concept of computational thinking to elementary school children using fun media, (2) Designing and developing a website-based computational thinking game, (3) Knowing the feasibility of a website-based computational thinking game in terms of functionality and interface effectiveness through usability testing methods. The type of research conducted was Research and Development (R&D) using the ADDIE model (Analyze), design, development, implementation, and evaluation. However, this research only reached the stage. The fourth is implementation. Usability testing was conducted on 10 class IV students at SDN Margaluyu, Sumedang Regency. The data analysis technique used is a quantitative descriptive technique. The research and development results are in the form of a website-based computational thinking game that gets a decent category with an average rating score of 4.07 from the effects of usability testing.